Rural revitalization potential and pathway optimization in Qinling poverty-alleviation mountainous areas under community resilience framework - GUO Yuexi, CHEN Jia, YIN Sha, YANG Xinjun, XIAO Yang (Ziyuan Kexue)
[Objective] Evaluating the potential of rural revitalization in the new era is a prerequisite for effectively connecting the consolidation of poverty alleviation achievements in poverty-alleviation mountainous areas with rural revitalization. Research on the potential and pathways of rural revitalization at the micro scale can provide theoretical support for rural revitalization practices. [Methods] Using Luonan County, Shaanxi Province as a case study, this study quantitatively evaluated rural revitalization potential and spatial distribution characteristics. The geodetector was used to identify the key influencing factors of rural revitalization potential in Luonan County, and a classification system for rural revitalization based on “potential grading and feature recognition” was developed. [Results] (1) Significant disparities in rural revitalization potential were observed among sample villages in the study area, with about 28% demonstrating relatively high rural revitalization potential. The average potential of rural environmental revitalization was the highest, while that of social revitalization was the lowest. Economic revitalization potential presented considerable room for improvement, and infrastructure revitalization potential displayed the greatest disparity. (2) Infrastructure was identified as the dominant factor influencing rural revitalization potential, with road density, leadership capacity, and household income-expenditure balance exhibiting strong interaction effects. (3) Based on the developed classification system for rural revitalization types, five village types were identified: prioritized revitalization, preparatory revitalization, gap-filling improvement, stability maintenance and decline prevention, and relocation and merger. [Conclusion] Based on the idea of “determining dominant factors and optimizing revitalization pathways”, this study proposes tailored rural revitalization pathways for the Qinling poverty-alleviation mountainous areas. Priority revitalization villages should extend the industrial chains and create rural IPs. Preparatory revitalization villages are expected to explore modern agricultural management as the main development direction. For villages of gap-filling improvement type, the construction and improvement of roads and agricultural infrastructure should be strengthened. Villages which focus on stability maintenance and decline prevention need to pay attention to farmers’ livelihood and implement differentiated planting. Villages of relocation and merger type should strengthen the ecological functions and values of the original villages, highlighting ecological restoration and conservation functions.